PENGUASAAN DALAM MENYELESAIKAN SOAL-SOAL MATEMATIKA BERKONTEKS SAPRAHAN SISWA SMPN JAWAI - Riezky Wahyu Handayani; Agung Hartoyo; Dede Suratman (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study was to describe the ethno-mathematics in the saprahan activities and to detrmine students mastery of material in solving mathematics problems in the saprahan context. The method used in this research is descriptive method. The subject are the students of VII A of SMPN 3 Jawai and the object is the mastery of the material in solving mathematics problems in the cotext of the saprahan. The data collection techniques used were written measurement techniques and direct communication techniques, so that the data collection tools used were test question, interview guidelines, and documents. Based on the results and discussion of ethno-mathematics in the saprahan activity, it includes five activities, namely 1) Merancap, relation to mathematical concept is the addition, 2) Bekaot, relation to mathematical concept is the addition and volume, 3) Ngator sajian, relation to mathematical concept is the plane, 4) Besurrong, relation to mathematical concept is the addition and plane, and 5) Bekakas, relation mathematical concept is the inequality. Of the five saprahan activities made in the form of questions, each questions consists of one saprahan activity. So that the results of the mastery of the material test in solving mathematics problems with the saprahan context has an average value of 68, while the average daily test results without the saprahan context is 52,94. This shows that students can solve math problems in the context of the greeting with good results compared to the form of questions they usually receive in school. Keywords: Ethno-matematics Saprahan, Mastery of The Material, Saprahan